PERTUMBUHAN TANAMAN SAWI (Brassica juncea L.) DENGAN PERENDAMAN KOLKISIN - Kamsia Dorliana Sitanggang; Siti Hartati Yusida Saragih; MHD Fadillah (JURNAL AGROPLASMA, 2021)
Brassica juncea is one of vegetable consumed by many people. One of the ways to expand genetic diversity is by inducing the occurrence of mutations. Mutations can be induced by offering chemical mutagens as well as physical mutagens. One of chemical have been successful to induce mutation is colchicine. The aim of this research was to determine effect of colchicine on Brassica growth. This research was conducted in June 2019 in the Experimental Field, Labuhanbatu University. The result show that soaking brassica seeds using colchicine make a decrease in the average plant height, leaf widht and number of leaves compare to control cause abnormal cell division. Keywords: Brassica juncea, Colchicine, Growth response